Optimization of process parameters for al-doping back ground on CO gas sensing characteristics of magnetron-sputtered TiO2 sensors. (23rd August 2019) - Vanmathi, M; Senthil Kumar, M; Ismail, M Mohamed; Senguttuvan, G
Abstract: Gas sensors used in automobiles needs to be operated at temperatures above 250 °C. Recently, high K-material TiO2 thin films have gained an important role as a high-temperature gas sensor. Al doped TiO2 thin films show maximum gas sensitivity at 600 °C. Fabrication of a sensor that operates at relatively low temperatures remains a big challenge for manufacturing of small size and low power consumption gas sensors. The operating temperature plays a crucial role in the performance of the gas sensors. The improved response to different gases is primarily attributed to the highly single crystalline surfaces. This paper investigates the process parameters influencing the Al doped TiO2 thin films deposited on silicon wafer substrate by using RF magnetron sputtering technique. The process parameters power, deposition time, substrate temperature and working pressure were selected to study the electrical resistivity, deposition rate and sensitivity. An orthogonal array L16 (4 4 ) was developed using Taguchi technique to study the effect of process parameters; signal-to-noise ratio (S/N) and analysis of variance (ANOVA). Confirmation tests identified the optimal depositional process parameters. ANOVA analyses indicate power, deposition time and substrate temperature showed substantial effect on thin film deposition. The optimum process parameters identified were 150 W power, 30 min deposition time, 150 °C substrate temperature and 1 Pa working pressure. At the operating temperature 400 °C, thin film samples annealed at 900 °C showed the lowest electrical resistivity and highest sensitivity for the 200 ppm CO gas concentration. The resistivity and sensitivity measured 5.31 × 10 −3 Ω-cm and 55% exhibited the best multiple performance characteristics of the Al doped TiO2 thin films. XRD results showed anatase structure was present as a single phase up to the annealing temperature 900 °C. Al doped TiO2 thin films stands out as a promising material for CO gas sensors.